Tarik Ulur Kewenangan Pusat dan Daerah dalam Penataan Ruang Proyek Strategis Nasional - Mukmin Zakie (Fakultas Hukum Universitas Islam Indonesia, 2023)
The National Strategic Project or better known as the PSN is a policy program that was born during the reign of President Joko Widodo. This program is highly prioritized because it is claimed to be able to help improve welfare and equitable development in various regions in Indonesia. The issue raised in this case is how the tug-of-war of central and regional authority in the spatial planning of the national strategic project (PSN). This research is normative legal research with statutory and conceptual approaches. The results of the research show that regions that have authority in the field of spatial planning according to the Regional Government Law and the Spatial Planning Law lose their authority in terms of controlling spatial use. In addition, there are potential conflicts, both conflicts between government agencies and conflicts with the community (land owners or communities affected by PSN development).